Analysis of disk cam motion for follower shape in vertical position - Mohd Rizal Hilmie, Abd Rahman (2008)
Cam is a mechanical component that translates movement from circular to reciprocating by using mating component, called the follower. The cam performance can be analyzed in vertical position to find time of one cycle, T, and the displacement of cam follower ∆R at the rotational angle, Ф. Every cam profile have it own performance and different from each other. This thesis is carried out to analyze the disk cam profile for the heart shape cam and tested in vertical position to find out it kinematics motion. In order to do the analysis, graphical method and experimental data are used to compare the error from the actual cam. The results from the analysis show that this cam is most suitable for low speed application because it show small error at low speed input.